2007
DOI: 10.1002/prot.21386
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella typhimurium YegS, a putative lipid kinase homologous to eukaryotic sphingosine and diacylglycerol kinases

Abstract: Salmonella typhimurium YegS is a protein conserved in many prokaryotes. Although the function of YegS is not definitively known, it has been annotated as a potential diacylglycerol or sphingosine kinase based on sequence similarity with eukaryotic enzymes of known function. To further characterize YegS, we report its purification, biochemical analysis, crystallization, and structure determination. The crystal structure of YegS reveals a two-domain fold related to bacterial polyphosphate/ATP NAD kinases, compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…However, there are numerous examples of enzymes that are located in the outer membrane of gram-negative bacteria, including a phosphomonoesterase (P4) and a glycerol-3-phosphodiester phosphodiesterase (protein D) in H. influenzae, an enolase in Pseudomonas aeruginosa, the lipid kinase YegS in Salmonella, and the lipid A acylase PagP and deacylase PagL found in Pseudomonas, Bordetella, and Salmonella (24,32,39,41,42,49). Additionally, the M. catarrhalis BRO-1 ␤-lactamase is in the outer membrane (12).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are numerous examples of enzymes that are located in the outer membrane of gram-negative bacteria, including a phosphomonoesterase (P4) and a glycerol-3-phosphodiester phosphodiesterase (protein D) in H. influenzae, an enolase in Pseudomonas aeruginosa, the lipid kinase YegS in Salmonella, and the lipid A acylase PagP and deacylase PagL found in Pseudomonas, Bordetella, and Salmonella (24,32,39,41,42,49). Additionally, the M. catarrhalis BRO-1 ␤-lactamase is in the outer membrane (12).…”
Section: Resultsmentioning
confidence: 99%
“…29,30 It was further suggested that the different conformational states of these two dimeric complexes could form the basis for a switching mechanism between partner proteins. StYeaZ has been reported to act as a resuscitation promoting factor (RPF) in Salmonellae, 31 Our studies are aimed at the characterization of the structure and biochemical properties of essential proteins of unknown function in Salmonella typhimurium that might represent novel drug targets, including YeaZ, 28 YegS, 33 and YcbL. 34 New drugs are urgently required as the continual rise of high level resistance to current anti-bacterials presents increasing threats to human and animal health.…”
mentioning
confidence: 99%
“…One is the DgkB structure mentioned above. The second is that of a Salmonella protein of undetermined function, YegS (32). Comparison of these structures has yielded insight into potential substrate-binding regions, sites of regulatory lipid(s) binding, sites of membrane binding, and conformational changes that could modulate activity.…”
Section: Structural Predictions From Prokaryotic Homologsmentioning
confidence: 99%
“…The YegS structure contains a hydrophobic region on the surface of Domain 1 that faces away from the substrate binding cleft (32). This region could represent a site for binding of lipids responsible for allosteric activation.…”
Section: Structural Predictions From Prokaryotic Homologsmentioning
confidence: 99%